Interkulturelle Kompetenz Deutschland-Russland 20 Critical Incidents mit Lösungmustern - Franzke, Bettina (W. Bertelsmann Verlag, 2017)
The reader is presented with 20 case examples, so-called Critical Incidents (CIs), which explain how to ensure a smooth encounter between Germany and Russia. The CIs promote empathy and the ability to switch perspectives. At the same time, they allow for new viewpoints in the context of German-Russian interactions. The publication addresses topics such as hospitality and welcoming culture, the expression of frustration and criticism, action processes, professional collaboration, external image, linguistic exchange, and approaches to overcome language barriers. Each of the 20 case examples from everyday life, school, and university are described by means of questions and possible solutions, which participants in language courses and exchange programmes as well as employees of international organisations can use to prepare themselves for short or long-term stays in Germany or Russia.